Kinetic study of copolymerization and terpolymerization of N-Carboxyanhydrides of ornithine, glycine and aspartic acid - Siyasanga, Mbizana (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.